1994
DOI: 10.1177/088307389400900208
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Intracranial Hypertension in Children: The Iowa Experience

Abstract: Idiopathic intracranial hypertension is an uncommon condition in children and is seen only about once a year in a large referral hospital. Sex incidence is equal, and obesity is a feature in about one third of patients. This article reviews the 30-year experience in an institution where idiopathic intracranial hypertension in adults has been extensively studied. Symptomatic causes of intracranial hypertension and both medical and surgical therapeutic options are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
124
1
11

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(146 citation statements)
references
References 68 publications
9
124
1
11
Order By: Relevance
“…1617 The finding of 45% having a weight beyond the 95th percentile for age is higher than Babikian, 15 but of similar magnitude. Despite opinion to the contrary, 16 our data suggest that obesity is present both in preadolescents and adolescents.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…1617 The finding of 45% having a weight beyond the 95th percentile for age is higher than Babikian, 15 but of similar magnitude. Despite opinion to the contrary, 16 our data suggest that obesity is present both in preadolescents and adolescents.…”
Section: Resultsmentioning
confidence: 89%
“…The association of obesity with idiopathic intracranial hypertension is not as strong for pediatric cases 15 as for those occurring within the adult population. 1617 The finding of 45% having a weight beyond the 95th percentile for age is higher than Babikian, 15 but of similar magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…without an underlying intracranial pathology. Headaches, vomiting and visual disturbances are common presenting symptoms of BIH [1]. In contrast to patients with intracranial mass lesions, consciousness and intellectual functioning remains normal in BIH [2].…”
Section: Case Reportmentioning
confidence: 99%
“…One study found that approximately 60% of children with IIH are older than 10 years. 4 There is no difference by sex in younger children; whereas IIH predominantly affects females if the diagnosis is in older children. For example, Balcer and colleagues found that 50% of 3-to 11-year-old children with IIH were female; 88% of children 12 to 14 years old; and 100% of children 15 to 17 years old.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…Children presenting with IIH commonly complain of a headache; 4,6 headache frequency and severity are variable. The headache may be worsened with Valsalva maneuvers and changes in posture.…”
Section: Symptoms and Signsmentioning
confidence: 99%